A Community-Based Cross-Sectional Study of Indoor Air Pollution and Its Mental Health Implications Among Rural Households - Sarma, Sreedhara Aditya; Pradeep TS (National Journal of Community Medicine, 2025)
Introduction: Emerging research indicates that air pollution can affect the central nervous system through various pathways, leading to inflammation and oxidative stress. This process leads to neurotoxicity and raises the risk of neurodevelopmental and neurodegenerative disorders, as well as anxiety and depression. Materials and methods: The present study is a cross-sectional study conducted over two years, involving rural households that use solid fuels. Air quality was measured using high-quality instruments. Mental health statuses such as anxiety and depression among residents of these households were assessed using standardized tools. The chi-square test was applied to examine associations, with a p-value less than 0.05 considered statistically significant. Results: Out of 812 residents, the majority belonged to the 31 to 40 years age group, male gender, a nuclear family, and the upper middle class of Modified BG Prasad Classification 2023. 25.6% had marked to severe anxiety, and 23.2% had mild depression. The AQI of rural households revealed that 192 (23.6%) were of poor standards as per the National guidelines. Anxiety and depression mental health status had a statistically significant association with AQI. Conclusion: The present study adds to the small but growing evidence indicating that exposure to indoor air pollution can be associated with mental health issues like Anxiety and Depression.